Penggunaan Media untuk Meningkatkan Hasil Belajar Guling Depan - Firmansyah, Arian Muhamad; Asmawi, Moch; Sukiri, Sukiri; Widiastuti, Widiastuti (Universitas Pendidikan Indonesia Kampus Sumedang, 2018)
This study aims to improve the results of forward roll learning in physical education through the use of media. This research is an action research research (classroom action research) with subject research is the third grade students of SDN Tengah 07 Pagi Jakarta Timur. This study was conducted for two cycles, each cycle consisting of two actions. Student learning result obtained from observation, interview, field notes and documentation. The results showed that learning by using media improves the learning forward roll, so that it can improve from cycle I as many as 14 students (60.9%) with an average score of 75.6 has reached the minimum mastery criteria (KKM) and 9 students (39.1%) has not reached the minimal minimum criteria. In the second cycle, it increased to 19 students (82.6%) who had reached the minimum completeness criteria, and 4 students (17.3%) with the average score of 78 not reaching the minimal minimum criteria. In this case has exceeded the mastery of individuals in both categories and has exceeded the criteria of classical learning completeness by 80%.